(untitled) - Paul, Clayton R. (New York, 1997)
This textbook contains 431 homework problems, answers to all problems are located at the end of the text for student reference, and gives you completely worked-out examples in order to make the concepts understanable and to demonstrate practical applications of the techniques.
Keywords: Electromagnetic fields